Mechanisms of Dyslipoproteinemias in Systemic Lupus Erythematosus. Issue 2 (2006) - Borba, Eduardo F.; Carvalho, Jozelio F.; Bonfá, Eloísa
Abstract : Autoimmunity and inflammation are associated with marked changes in lipid and lipoprotein metabolism in SLE. Autoantibodies and cytokines are able to modulate lipoprotein lipase (LPL) activity, a key enzyme in lipid metabolism, with a consequent "lupus pattern" of dyslipoproteinemia characterized by elevated levels of very low-density lipoprotein cholesterol (VLDL) and triglycerides (TG) and lower high-density lipoprotein cholesterol (HDL) levels. This pattern favors an enhanced LDL oxidation with a subsequent deleterious foam cell formation. Autoantibodies and immunocomplexes may aggravate this oxidative injury by inducing accumulation and deposition of oxLDL in endothelial cells. Drugs and associated diseases usually magnify the close interaction of these factors and further promote the proatherogenic environment of this disease.